Spatial Diversity in the Socio-Economic Development in Sub-Saharan Africa as Measured by a Composite Index - Witoń, Agnieszka (Entrepreneurial Business and Economics Review, 2015)
The main aim of the article is to present the level of the socio-economic development in Sub-Saharan Africa's sub-regions: West Africa, South Africa, East Africa, and Central Africa. The second aim is to identify whether some of the sub-regions have significantly different level of the socio-economic development in comparison to the others.A composite index of development has been created. Hypotheses are verified through statistical analysis (including parametric tests).Sub-Saharan countries do not differ significantly in the socio-economic development level. No sub-region has a significantly higher (or lower) level of development in comparison to the others. However, after eliminating Seychelles from the analysis (as an outlier value) East Africa proves to be significantly lower developed than the whole region and other sub-regions.The lack of significant differences in the level of the socio-economic development in Sub-Saharan countries proves that analysing them as one group is justified.A new composite index of the socio-economic development has been created to test the hypotheses.